A Companion to Greek Art. - Smith, Tyler Jo (John Wiley & Sons, 2012)
A comprehensive, authoritative account of the development Greek Art through the 1st millennium BC. An invaluable resource for scholars dealing with the art, material culture and history of the post-classical worldIncludes voices from such diverse fields as art history, classical studies, and archaeology and offers a diversity of views to the topicFeatures an innovative group of chapters dealing with the reception of Greek art from the Middle Ages to the presentIncludes chapters on Chronology and Topography, as well as Workshops and TechnologyIncludes four major sections: Forms, Times and Places.